Tissue distribution of a plasmid DNA encoding Hsp65 gene is dependent on the dose administered through intramuscular delivery - Coelho-Castelo, A. A M; Trombone, A. P.; Rosada, R. S.; Santos, R. R.; Bonato, V. L D; Sartori, A. [UNESP]; Silva, C. L. (Springer Nature, 2006)
In order to assess a new strategy of DNA vaccine for a more complete understanding of its action in immune response, it is important to determine the in vivo biodistribution fate and antigen expression. In previous studies, our group focused on the prophylactic and therapeutic use of a plasmid DNA encoding the Mycobacterium leprae 65-kDa heat shock protein (Hsp65) and achieved an efficient immune response induction as well as protection against virulent M. tuberculosis challenge. In the present study, we examined in vivo tissue distribution of naked DNA-Hsp65 vaccine, the Hsp65 message, genome integration and methylation status of plasmid DNA. The DNA-Hsp65 was detectable in several tissue types, indicating that DNA-Hsp65 disseminates widely throughout the body. The biodistribution was dose-dependent. In contrast, RT-PCR detected the Hsp65 message for at least 15 days in muscle or liver tissue from immunized mice. We also analyzed the methylation status and integration of the injected plasmid DNA into the host cellular genome. The bacterial methylation pattern persisted for at least 6 months, indicating that the plasmid DNA-Hsp65 does not replicate in mammalian tissue, and Southern blot analysis showed that plasmid DNA was not integrated. These results have important implications for the use of DNA-Hsp65 vaccine in a clinical setting and open new perspectives for DNA vaccines and new considerations about the inoculation site and delivery system. © 2006 Coelho-Castelo et al; licensee BioMed Central Ltd.
Keywords: DNA vaccine; heat shock protein 65; plasmid DNA; animal experiment; animal tissue; controlled study; DNA isolation; DNA methylation; dose response; drug distribution; genome; immunization; in vivo study; liver; mouse; muscle tissue; nonhuman; reverse transcription polymerase chain reaction; RNA isolation; Southern blotting; tissue distribution; viral gene delivery system; Animalia; Bacteria (microorganisms); Mammalia; Mycobacterium leprae